Nieliniowe Zagadnienie Stateczności Sprężystej Trójwarstwowej Otwartej Powłoki Walcowej - Szyc, W. (Engineering Transactions, 1971)
In this paper is solved the nonlinear problem of an elastic buckling of a sandwich open cylindrical shell under the influence of compressing forces applied to simply supported edges of a shell. The equations of the equilibrim and boundary conditions are obtained, on the basis of the hypothesis of a «broken line», from the condition of minimum potential energy of a set. Solution of these equations is based on the Bubnov-Galerkin method. Upper and lower values of the critical load are obtained in a general manner. The paper also contains the results of numerical examples made for shells with a light filling compressed along the generating lines. Analysis is made of the influence of certain geometrical and physical parameters of the shell on the stability loss process and on the critical loading values.